Health care expenditure in the Islamic Republic of Iran versus other high spending countries - Khosravi, Bahman (Med J Islam Repub Iran, 2017)
Background: In all countries, health expenditures are a main part of government expenditure, and governments try to find policies and strategies to reduce this expenditure. Overall expenditure index has been raised 30 times during the past 20 years in Iran, while in the health sector, the growth in health expenditures index has been 71 times. The present study aimed at examining health care expenditure in the Islamic Republic of Iran versus other high spending countries. Methods: A comparative panel study was conducted in selected countries with the high mean of health expenditure per capita. Data were collected from the WORLD BANK. Out- of- pocket (OOP), health expenditure per capita, public and private health expenditure, and total health expenditure were compared among the selected counties. Results: Iran has the lowest health expenditure per capita compared to other countries and the USA has the highest health expenditures per capita. In Iran, out- of- pocket expenditure, with more than 50%, was the most cost, while in Luxembourg it was the least cost during 2004 to 2014, with less than 12%. Conclusion: Our findings revealed that politicians and health care executives should find a stable source to finance the health system. Stable sources of financing lead to having a steady trend in health expenditure.